ANALISIS AGRIBISNIS KENTANG (Solanum tuberosum L) Desa: Merek, Kecamatan Merek, Kabupaten Karo, Provinsi Sumatera Utara - Lilis S. Gultom; Damai Zaro Gea (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
The aim of the research are (1) knowing the internal and external factors which are strengths, weaknesses, opportunities and threats in the development of potato agribusiness.), (2) knowing the alternatives and priorities that can be applied in the development of potato agribusiness, (3) knowing how much cost, revenue, and income of potato farming, (4) knowing Knowing the feasibility of potato farming in the study area.The research area was determined by the purposive sampling of Trademark, Trademark District, Karo District which was conducted in May 2019 - August 2019. The reason for choosing the area was because the majority of the population were cultivating potato plants. The sampling method is done by simple ranom sampling (simple random). The sample in this study were farmers who worked on potato crops throughout the year. The number of samples in this study amounted to 30 samples. The results showed that: There are internal and external factors that become strengths, weaknesses, opportunities, and threats in the development of potato agribusiness in the study area. Based on the results of the QSPM matrix analysis of the eight strategies there is one strategy that needs to be prioritized with a TAS value of 5,893. Costs used by farmers in managing their farms are Rp.17,099,180 per farmer. Revenue per farmer is Rp.59,500,000. The level of income of potato farmers in the study area is relatively high. Where the net income per farmer is Rp.42,400,820, while the R/C value of potato farming is 3.48 per farmer, this shows that the R/C ratio is greater than one so that the potato farming is feasible (economically profitable).